Tindak Tutur Asertif dalam Indonesia Lawyers Club (ILC) - Shaflaini Salma (Nuances of Indonesian Language, 2022)
This research is motivated by the use of language in the Indonesia Lawyers Club (ILC) event on TvOne. Focusing on four episodes at the Indonesia Lawyers Club (ILC). Debates and discussions at the Indonesia Lawyers Club (ILC) show the opinions of each invited resource who convey ideas to strengthen their arguments in various ways of conveying. This study aims to describe speech acts. assertive in the Indonesia Lawyers Club (ILC) on TvOne (pragmatic study). This type of research is qualitative-descriptive by collecting data using documentation techniques by downloading videos on the official TvOne website. Furthermore, using the listening method with the basic technique of listening to the free to engage proficiently because the researcher listens to the use of language during the discussion and the technique of taking notes on the data inventory table. The data that has been collected is then analyzed in three steps, namely: data reduction, data presentation, and conclusion or verification. In the data analysis, the researcher also used the equivalent method, the change method with the dressing technique, and the markup reading method to determine the classification of speech acts.